Kajian Administrasi Perencanaan Transportasi Perkotaan Berbasis Sinergi Pemerintah Kota, Bhabinkamtibnas, dan Perguruan Tinggi (Studi Kasus Kota Surabaya) - Fitri Ambarwati; Ismail Ismail (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2018)
The objectives of the study were to describe and plan urban transfers planning based on city government synergy, bhabinkamtibnas and universities. This research uses descriptive qualitative research method. In the planning of city government synergy, bhabinkamtibnas, and universities in carrying out transpotation planning, can be seen from the planning, implementation actors, programs, and facilities and infrastructure. Kareana synergy will bring positive results to the people of Surabaya city in terms of various aspects. In this research it is concluded that the implementation of transportation planning in the city of Surabaya is expected to be able to synergize with Bhabinkamtib- nas, and universities in order to realize a sustainable and more effective concept.